Electric power distribution - Pabla A. S. (McGraw-Hill professional engineering, 2005)
This hands-on engineering resource expertly addresses the challenges confronting today's electric utilities. Written by the former chief engineer of a large electricity system, this comprehensive text provides crucial information on avoiding power reductions and failures, and meeting tests posed by new technologies and greater loads, maintenances issues, and privatization.